Flexoid Tubing and Its Application to Coal Mines As a Means of Temporary Ventilation - George A. Brown (Rocky Mountain Coal Mining Institute, 1921)
Flexoid tubing for ventilation and some of the reasons for its use in re-opening old workings at the Union Pacific Coal Company's mines at Cumberland, Wyoming. , These mines are located on a branch line off the Oregon Short Line Railroad, about sixteen miles south of Kemmerer. The seam averages from 16 feet to 20 feet thick and is split about six feet from the bottom with from six inches to four inches of fire, clay; and is covered by a heavy sandstone roof about 45 feet thick and a fire clay floor about 15 feet thick. Pitch of seam 21 degrees. These mines were opened up with 5 openings on the pitch to the west, with main slope, north and south manways and north and south aircourses on 50-foot centers with parallel entries driven north and south at right angles to the slope and rooms turned on 50-foot centers up the pitch ; entries being 350 feet apart and chutes used in the rooms. Several years ago there was a heavy, squeeze came on these mines which necessitated shutting down all of No. I Mine below the third entry, the slope being down to 12 entry; also shutting the lower end of No. 2 Mine down from the twelfth entry to fifteenth entry and from the third entry down to the tenth entry, so as not to work too much territory at the one time. These mines are very gassy and were subject to heavy bumps during the squeeze ; also at the present time. In reopening these slopes, aircourses and entries for the recovery of the pillars, ventilation was quite a problem, as the squeeze had caused them to be practically tight; also the rooms for about 50 feet from the entry and the face of the rooms for about fifty feet. These rooms in the open space being either filled with Methane or depleted air. It was found in opening up these entries that in driving back entries parallel with the top entries for ventilation. which had to be skipped along the barrier pillar left from the face of the rooms of the entry below, that we had more bumps or bounces which made it a dangerous proposition to nine, as it will be noted as stated that the entries, room necks and face of rooms were more or less squeezed tight, showing that all the weight was centered on these points and the more they were disturbed the more it relieved the overlying pressure and something had to give; hence the bumps or bounces which have filled slopes, aircourses, entries and rooms with coal from the ribs and face, for hundreds of feet, throwing cars off the track, both loads and empties, and throwing track up to the roof and discharging timbers. We found it necessary to abandon driving back entries and have used Flexoid tubing with small blower fans to open up these slopes, aircourses and entries which has proved a success. We have carried air for distances that would have been impossible with brattice cloth or with